(5+x)-6=7

Simple and best practice solution for (5+x)-6=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5+x)-6=7 equation:


Simplifying
(5 + x) + -6 = 7

Remove parenthesis around (5 + x)
5 + x + -6 = 7

Reorder the terms:
5 + -6 + x = 7

Combine like terms: 5 + -6 = -1
-1 + x = 7

Solving
-1 + x = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + x = 7 + 1

Combine like terms: -1 + 1 = 0
0 + x = 7 + 1
x = 7 + 1

Combine like terms: 7 + 1 = 8
x = 8

Simplifying
x = 8

See similar equations:

| 2(10*2)=30+10 | | 3x-44=56-2x | | x/12-15=36 | | -3n=-5 | | 40=3/4x-32 | | 2(10*10)=30+10 | | 21-3=18 | | 21x+7=3x+1621-3 | | 2x/8-3/4=5/12 | | 5+8m=7m+2 | | -9a-3=-36 | | 5-8x=16-8 | | 1+(6)(8)= | | N-7=-3+2n | | 39x+33=501 | | 2x-3=2x+10 | | (1/5)^2x=125 | | 2x+2y=990 | | 8/19 | | 5(4+r)=.5(40+10r) | | M+3=9+3m | | w=m+6 | | 4x-9+17=3x+5 | | w=5m-10 | | 4(2)(2)= | | -4(6x-3)= | | 6=2/3x-6 | | 6x+25=16-3x | | 27-10x=7 | | (X-4)(x+9)=(x+5)(x-3) | | 12x+7=15x-14 | | 3x=288x |

Equations solver categories